Sobre Francisco Chacón Jiménez, Antonio Irigoyen, Eni de Mesquita Samara y Teresa Lozano Armendares (eds.), Sin distancia. Familia y tendencias historiográficas en el siglo XX - Roselló Soberón, Estela (El Colegio de México, A.C., 2005)
-